Interaction of laser radiation with matter : Peculiarities of the formation of an ensemble of photonic nanojets by a micro-assembly of conical particles. (15th March 2019) - Geints, Yu E; Zemlyanov, A A; Panina, E K
Abstract: We report the results of theoretical studies on spatially localised near-field light structures (photonic nanojets) arising during the scattering of laser radiation on a metasurface in the form of a single-layer ordered assembly of dielectric microcones embedded in a transparent matrix (silicone film). By solving Maxwell's equations using the method of computational electrodynamics, basic parameters of localised light structures (length, width, and peak intensity) are analysed in detail under the conditions of mutual influence of the light fields of adjacent microparticles. It is found that the main factors affecting the characteristics of photon nanojets in question are the spatial orientation of microcones and the degree of their embedding into the silicone matrix. It is shown that a number of spatial configurations of conical micro-assemblies allow the formation of an ensemble of photon nanojets with specific characteristics unattainable for isolated microcones.